The New Financial Accounting System In Algeria; The Horizons And The Challenges - Slimane, Sefiane (جامعة الوادي - University of Eloued, 2011)
The purpose of this paper is to provide some insights on the Algerian Accounting System . Its particular purpose is to provide a historical background which have led to the formation of Accounting System in Algeria, taking into account the introduction of the new accounting standards and the emerging new financial accounting system . Then discusses the relevancy of the new financial accounting system to the new economic climate in Algeria. Finally, the paper concludes that since the new financial accounting system is kept uniform, the new financial and accounting system in Algeria may not be progressive towards cost and management accounting, and hence further efforts are needed to develop it
مقال
Keywords: Economic Reforms, Accounting Reforms, International Accounting Standards, Cost and Management Accounting.